Multi-User Adaptive Resource Allocation Scheme for WLAN OFDM-MIMO Transmission - Malathi, P; Vanathi, P. T. (INFOCOMP Journal of Computer Science, 2008)
Orthogonal Frequency division multiplexing (OFDM) has recently been proposed for use in high data-rate wireless systems. OFDM has an important property of spectrum utilization technique that distributes each tone, which is orthogonal with every other tone. The system capacity can be significantly improved by multiple transmit and receive antennas that are used to form Multi-input multi-output (MIMO) channel. The combination of OFDM with MIMO transmission performance can be vastly improved by properly allocating the resources amongst different users. For that this paper proposes a multi-user Adaptive resource allocation scheme for Wireless Local Area Network (WLAN) transmission. Based on the channel information and power level, resource allocation algorithm assigns a set of subcarriers to each user and loads the corresponding subcarriers with different number of bits per OFDM symbol subject to resultant BER which should not be higher than target BER. The main objective of this proposed algorithm is to maximize the overall data rate of the channel. The improved performance of this system is compared with fixed resource allocation TDMA scheme and the simulation result shows that the minimum user’s capacity is appreciably improved compared to the TDMA scheme..